2012
DOI: 10.18227/1982-8470ragro.v6i1.683
|View full text |Cite
|
Sign up to set email alerts
|

Plantas daninhas em área de reforma de cana crua com diferentes manejos do solo e adubos verdes em sucessão

Abstract: Resumo -A renovação dos canaviais é importante para manter elevada a produtividade agrícola da cultura e é realizada em média após cinco cortes, com o objetivo de comparar o efeito residual das culturas de sucessão nos diferentes sistemas plantio sobre a ocorrência espontânea de plantas daninhas em área de reforma de cana crua, instalou-se o experimento sobre ARGISSOLO VERMELHO-AMARELO Eutroférrico, localizado no município de Novais-SP, em canavial colhido sem queima prévia nos últimos cinco cortes. Utilizou-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Soares et al (2012) have found similar results in work comparing soil management and crop rotation with green manures. The decrease of the nutsedge importance when peanuts are grown in succession to sugarcane may be due both to the dampening provided by the vegetation cover as the residual effect of imazapic applied in peanut crops, for the transposition of imazapic through sugarcane straw is highly significant (Ferreira et al, 2010).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Soares et al (2012) have found similar results in work comparing soil management and crop rotation with green manures. The decrease of the nutsedge importance when peanuts are grown in succession to sugarcane may be due both to the dampening provided by the vegetation cover as the residual effect of imazapic applied in peanut crops, for the transposition of imazapic through sugarcane straw is highly significant (Ferreira et al, 2010).…”
Section: Resultssupporting
confidence: 62%
“…However, while raw sugarcane harvest presents agronomic benefits, a lot of waste left on the surface and the intense mechanization of the area may reduce the sugarcane plantation longevity (Soares et al, 2012). Sugarcane fields renovation is performed on average after five sugarcane crops, and in most cases these areas remain in fallow during the period between the sugarcane harvest and the implementation of the new sugarcane field.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly used legumes was velvet bean (Mucuna aterrima), mostly due to its green manure properties (AMBROSANO et al, 2013) and high vigor, being able to suppress the establishment of some weed species (SOARES et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This result is mainly owing to the physical effect of joint smothering and reduction of light availability by the green manure species (Soares et al. ). Greater light availability for the soil favors the spread of invasive grasses because they are highly intolerant to shading (Meschede et al.…”
Section: Discussionmentioning
confidence: 99%
“…The arrangement with green manure and native species mixed favors greater vegetation cover, and thus reduces the presence and establishment of invasive grasses. This result is mainly owing to the physical effect of joint smothering and reduction of light availability by the green manure species (Soares et al 2012). Greater light availability for the soil favors the spread of invasive grasses because they are highly intolerant to shading (Meschede et al 2007, Pereira et al 2012).…”
Section: Discussionmentioning
confidence: 99%